2017
DOI: 10.1021/acs.jpcc.7b03305
|View full text |Cite
|
Sign up to set email alerts
|

Canonical, Deprotonated, or Zwitterionic? A Computational Study on Amino Acid Interaction with the TiO2 (101) Anatase Surface

Abstract: The interaction of 11 amino acids with the TiO2 (101) anatase surface was investigated by means of PBE-D2* periodic simulations, both from a static and dynamic points of view. Several adsorption states, with the amino acid in its canonical, zwitterionic, or deprotonated forms, were considered. The strongest interactions correspond to dative interactions between the electron pairs of N or O atoms of the amino acids and the Ti atoms of the surface. For glycine, the most stable configuration corresponds to the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…That is, Ti atoms can accept lone pairs of donor atoms (e.g., N or O), whereas O surface atoms can become Brønsted bases by accepting protons released by acidic compounds. This is indeed the case for glycine, which on the (101) anatase surface spontaneously transfers the −COOH proton to the surface giving rise to a glycine − /surface + ion pair . In this work, kinetic and thermodynamic effects of the TiO 2 (101) anatase surface, caused by the presence of Ti Lewis and O Brønsted sites, for the peptide‐bond formation between two glycine molecules is demonstrated by periodic DFT‐D2 simulations.…”
Section: Introductionmentioning
confidence: 99%
“…That is, Ti atoms can accept lone pairs of donor atoms (e.g., N or O), whereas O surface atoms can become Brønsted bases by accepting protons released by acidic compounds. This is indeed the case for glycine, which on the (101) anatase surface spontaneously transfers the −COOH proton to the surface giving rise to a glycine − /surface + ion pair . In this work, kinetic and thermodynamic effects of the TiO 2 (101) anatase surface, caused by the presence of Ti Lewis and O Brønsted sites, for the peptide‐bond formation between two glycine molecules is demonstrated by periodic DFT‐D2 simulations.…”
Section: Introductionmentioning
confidence: 99%
“…In this Hessian matrix, only the dyes and the first layer of the surface were considered. This methodology confirmed that the optimized structures were minimal, and enabled the calculation of the free energy G at T = 298.15 K. For this purpose, a script was used, which calculated the quasi‐harmonic thermochemical corrections. Specifically, the entropy S was computed in terms of the vibrational (harmonic oscillator approximation) and rotational (quasi‐RRHO approach) entropies, in addition to a damping function, as it has been described by Grimme, while the enthalpy H was obtained through H = U + PV , where P was given by the total energy change in function of the volume cell optimized.…”
Section: Models and Computational Detailsmentioning
confidence: 81%
“…In addition to glycine (Gly), four amino acids with sidechains that have the distinct physiochemical properties were subject to p‐DFT calculations, as valine (Val), proline (Pro), arginine (Arg), and aspartic acid (Asp), see Scheme . Pro is the only natural amino acid with the secondary N atom and often results in the β‐turn structures in peptides and proteins.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In addition to glycine (Gly), four amino acids with sidechains that have the distinct physiochemical properties were subject to p-DFT calculations, as valine (Val), proline (Pro), arginine (Arg), and aspartic acid (Asp), see Scheme 1. [24,44] Pro is the only natural amino acid with the secondary N atom and often results in the β-turn structures in peptides and proteins. Three representative isomers of amino acids reported previously [14,18,29] become the focus of this study (Scheme 2): For all amino acids, zwitterions (A) are the principal conformations in aqueous solutions and are the active form to conduct the biological and pharmaceutical functions.…”
Section: Modelsmentioning
confidence: 99%
See 1 more Smart Citation